2023
DOI: 10.1002/biof.2013
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of vitamin D in an Alzheimer's disease rat model: Improvement of mitochondrial dysfunction via calcium/calmodulin‐dependent protein kinase kinase 2 activation of Sirtuin1 phosphorylation

Marwa Mohanad,
Shimaa K. Mohamed,
Basma E. Aboulhoda
et al.

Abstract: Mitochondrial dysfunction is an early event in Alzheimer's disease (AD) pathogenesis. To assess the impact of vitamin D3 (Vit.D) on neurogenesis, we investigated its role in mitigating cognitive impairment and mitochondrial dysfunction through calcium/calmodulin‐dependent protein kinase kinase 2 (CAMKK2)‐mediated phosphorylation of Sirtuin1 (SIRT1) in an aluminum‐chloride‐D‐galactose (AlCl3‐D‐gal)‐induced AD rat model. Rats were distributed into four groups: control, AlCl3 + D‐gal (10 + 60 mg/kg, ip), Vit.D (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 88 publications
(187 reference statements)
0
1
0
Order By: Relevance
“…The regulation of mitochondrial function has been seen as helpful in reversing age-related hypertension in young male mice [ 85 ]. Again, due to the known role of mitochondria in neurodegeneration and Alzheimer’s disease in particular, Mohanad et al found that VitD was able to improve the oxidative stress and mitochondrial function in a preclinical model of induced AD, through calcium/calmodulin-dependent protein kinase kinase 2 (CAMKK2)-mediated phosphorylation of Sirtuin1 (SIRT1) [ 86 ].…”
Section: Vitamin D and Its Potential Impact On The Biological Hallmar...mentioning
confidence: 99%
“…The regulation of mitochondrial function has been seen as helpful in reversing age-related hypertension in young male mice [ 85 ]. Again, due to the known role of mitochondria in neurodegeneration and Alzheimer’s disease in particular, Mohanad et al found that VitD was able to improve the oxidative stress and mitochondrial function in a preclinical model of induced AD, through calcium/calmodulin-dependent protein kinase kinase 2 (CAMKK2)-mediated phosphorylation of Sirtuin1 (SIRT1) [ 86 ].…”
Section: Vitamin D and Its Potential Impact On The Biological Hallmar...mentioning
confidence: 99%